An open‐label, single‐arm, phase 2 trial of the polo‐like kinase inhibitor volasertib (BI 6727) in patients with locally advanced or metastatic urothelial cancer. Issue 7 (11th December 2013) - Stadler, Walter M.; Vaughn, David J.; Sonpavde, Guru; Vogelzang, Nicholas J.; Tagawa, Scott T.; Petrylak, Daniel P.; Rosen, Peter; Lin, Chia‐Chi; Mahoney, John; Modi, Sanjiv; Lee, Peter; Ernstoff, Marc S.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Polo‐like kinases (Plks) control multiple steps during the cell cycle, and Plk1 is overexpressed in urothelial cancer (UC). Volasertib (BI 6727), a Plk inhibitor, has demonstrated antitumor activity in several malignancies, including UC. In this phase 2 trial, the authors investigated volasertib as a second‐line treatment in advanced/metastatic UC. METHODS Patients who progressed within 2 years of 1 prior chemotherapy regimen received 300 mg volasertib on day 1 every 3 weeks. The dose was escalated to 350 mg in cycle 2 if volasertib was tolerated in cycle 1. The primary endpoint was tumor response, which was assessed every 6 weeks; secondary endpoints were progression‐free survival, overall survival, duration of response, safety, and pharmacokinetics. RESULTS Fifty patients were enrolled, and the median patient age was 68.5 years (range, 52‐83 years). All patients had received prior platinum, 94% of patients had relapsed ≤2 years after prior therapy, 36% had liver metastases, and 54% had lung metastases. The median number of treatment cycles was 2 (range, 1‐27 treatment cycles), and 23 patients were dose escalated at cycle 2. Seven patients (14%) had a partial response, 13 (26%) had stable disease, and 30 (60%) progressed within 6 weeks. The median response duration was 41 weeks (range, 29.1‐77.3 weeks). The median progression‐free survival was 1.4 months, and the median overall survival was 8.5 months. The most frequent grade 3 and 4 adverse events were neutropenia (28%), thrombocytopenia (20%), and anemia (16%). No cumulative toxicity was observed. CONCLUSIONS Volasertib as second‐line treatment for advanced/metastatic UC had an acceptable safety profile but demonstrated insufficient antitumor activity for further evaluation as a monotherapy. Cancer 2014;120:976–982. © 2013 American Cancer Society.